Neonatal-Maternal Attachment and Self-compassion in Postpartum Period - Masoumeh Kordi; soheila mohamadi (Mashhad University of Medical Sciences, 2018)
Background: between mother and her neonatal reflects the quality of maternal emotional feelings and behaviors toward her baby. This attachment emerges in behaviors, which indicate the mother's attention and care. Self-compassion is the extension of compassion to oneself in instances of perceived inadequacy, failure, or general suffering. Regarding this, the aim of the present study was to determine the relationship between maternal-neonatal attachment and self-compassion in postnatal period.Methods: This cross-sectional study was conducted on 335 primiparous women, referring to health care centers in Mashhad city in 2014. The study population was selected using the cluster and convenience sampling methods. The research tools were maternal/neonatal demographic form, self-compassion scale, and neonatal-maternal attachment questionnaire. The data were analyzed by Pearson correlation coefficient and linear regression model in SPSS software (version 22).Results: The results of the Pearson correlation coefficient test showed a positive correlation between the total score of maternal-neonatal attachment and self-compassion in postpartum period (r=0.22, P=0.012). Accordingly, as the score of self-compassion increased, the maternal-neonatal attachment score also enhanced.Conclusion: As the findings indicated, there was a correlation between self-compassion and maternal-neonatal attachment in postnatal period. Therefore, the provision of caregivers with education regarding psychological problems by community health midwives during postnatal period can be effective in the early diagnosis and identification of such disorders